New familial assignments for three species of Neotropical harvestmen based on cladistic analysis (Arachnida: Opiliones: Laniatores) - Pinto-Da-Rocha, Ricardo; Hara, Marcos Ryotaro (Zootaxa, 2009)
We herein propose transfer of the two monotypic genera Globibunus (type-species G. rubrofemoratus Roewer, 1912) and Rivetinus (type-species R. minutus Roewer, 1919) to the subfamily Zamorinae (Agoristenidae) and Ramonus (typespecies R. conifrons Roewer, 1956), previous placed in Agoristenidae, to the Prostygninae (Cranaidae) based on several characteristics of male genitalia. These transfers are corroborated by a cladistic analysis, which also recovered the three currently recognized agoristenid subfamilies.